A Genre Analysis of the Texts in English Textbook “Pathway To English” Used by Tenth Grade Students - Johan, Andrian Nuriza; Krismono, Gunawan Panji; Triana, Juita (English Education and Literature Journal (E-Jou), 2022)
This study aims to find out the text genres, the generic structure and language features in English textbook Pathway to English used by tenth grade students. This study analyzed the genre of the text, generic structure, and language features. A descriptive qualitative method is used to analyze the genre in Pathway to English textbook. There were four genres found in collecting data, descriptive text, narrative text, recount text, and announcement text. Then the researcher analyzing the generic structure and language features used in the text. After analyzing the data, the researcher found that from 18 texts taken, 4 texts (22%) data were descriptive text, 5 texts (28%) data were narrative text, 5 texts (28%) data were recount text, and 4 texts (22%) data belonged to announcement text. Based on the theories, the generic structure and the language features of each genre found in Pathway to English textbook were correct in English. Keywords: genre, text, textbook